Using Discrete Event Simulation in multiple System Life Cycles to support Zero-Defect Composite Manufacturing in Aerospace Industry. Issue 13 (2019) - Steringer, Robert; Zörrer, Helmut; Zambal, Sebastian; Eitzinger, Christian
Abstract: Visual inspections performed by operators are very time-consuming in the manufacturing process of carbon fibre parts in aerospace industry In the EU research project ZAero (Zero-defect manufacturing of composite parts in the aerospace industry) in-situ manual inspection on fibre placement stations thus shall be replaced by automatic inline inspection. To quantify the improvements of the suggested process changes, a series of experiments performed by a discrete event simulation (DES) model was needed to provide necessary key performance indicators (KPI). As the new inline inspection detects events and provides a lot of additional data for them, the simulation model proved to be very useful to support a decision support system (DSS) to help decision makers in determining which of the events count as defects and need to be reworked. In our work we show that a DES model, when properly implemented, is as versatile as a Swiss knife and can make valuable contributions to more than one life cycle of manufacturing systems.